In Vitro Antiparasitic and Apoptotic Effects of Antimony Sulfide Nanoparticles on Leishmania infantum - Saied Soflaei; Abdolhossein Dalimi; Fatemeh Ghaffarifar; Mojtaba Shakibaie; Ahmad Reza Shahverdi; Mohsen Shafiepour (Journal of Parasitology Research)
Visceral leishmaniasis is one of the most important sever diseases in tropical and subtropical countries. In the present study the effects of antimony sulfide nanoparticles on Leishmania infantum in vitro were evaluated. Antimony sulfide NPs (Sb2S5) were synthesized by biological method from Serratia marcescens bacteria. Then the cytotoxicity effects of different concentrations (5, 10, 25, 50, and 100 μg/mL) of this nanoparticle were assessed on promastigote and amastigote stages of L. infantum. MTT method was used for verification results of promastigote assay. Finally, the percentages of apoptotic, necrotic, and viable cells were determined by flow cytometry. The results indicated the positive effectiveness of antimony sulfide NPs on proliferation of promastigote form. The IC50 (50% inhibitory concentration) of antimony sulfide NPs on promastigotes was calculated 50 μg/mL. The cytotoxicity effect was dose-dependent means by increasing the concentration of antimony sulfide NPs, the cytotoxicity curve was raised and the viability curve of the parasite dropped simultaneously. Moreover, the IC50 of antimony sulfide NPs on amastigote stage was calculated 25 μg/mL. On the other hand, however, antimony sulfide NPs have a low cytotoxicity effect on uninfected macrophages but it can induce apoptosis in promastigote stage at 3 of 4 concentrations.